PELEMBAGAAN USAHA BERSAMA KERUPUK “MENARA” BERBASIS MASYARAKAT DI KESUGIHAN KIDUL, KABUPATEN CILACAP - Chamid Sutikno; Zaula Rizqi Atika; Ariesta Amanda; Shadu Satwika Wijaya; M.H. Maab (Department of Public Administration, University Wijaykusuma Purwokerto, 2023)
Poverty alleviation as mandated a top priority in the implementation of national development. The government is obliged to improve the level of welfare, quality, and survival of the community as well as to increase the ability and awareness of the community in the implementation of social welfare in an institutionalized and sustainable manner. In practice, social welfare can be achieved by empowering the community and increasing the participation of institutions and/or individuals as potentials and resources in the implementation of social welfare. Based on the concept of institutionalization of the Esman program, Social Welfare is a form of program that must be carried out in an institutionalized manner so that maximum results are obtained, namely through a transaction process between institutional variables, such as leadership, doctrine, resources, programs, and internal structures, with several related links. around the program. The effort to develop the Tower Cracker Business in Kesugihan Kidul village - Cilacap into a joint effort, is a form of community powerlessness in improving social welfare because it does not get full support from all elements of society. Based on this, the presence of community service regarding